El mensaje de la gracia. Vida de María y vocación de la Iglesia (2016)
The topic of this article is very broad and, therefore, needs some clarification. It is about rethinking the entire Christian soteriology, from the Mariology and Marian point of view and, although not directly explicit, this is done in the context of our time and current ecclesial life. Probably, no dimension of Christian life is so directly interested in the understanding people have of themselves as soteriology, and; however, no other aspect of faith is as difficult and strange to the common feeling as the gift of salvation (Werbick, 1990). To explain this lack of interest regarding the Christian soteriology, many factors should be remembered , but the key point relates to the interpretation of life naively attributed to the Christian conception. Not few interpret Christian salvation basing it on a dark and negative scenario of a world dominated by sin and its expressions of violence, evil, injustice, immorality; through punishment and the gift of grace, God would educate humanity and would progressively introduce it in the life that pleases Him.